The DC Electrical Resistivity Curves of Bismuth-2212 Ceramic Superconductors: Evaluation of the Hole-Carrier Concentrations per-Cu Ion - nurmalita . (Journal of Aceh Physics Society, 2016)
In this study the samples of Bismuth ceramic superconductors were synthesized by the melt textured growth methods from a 2212 stoichiometric composition in order to obtain a large amount of pure Bi-2212. The effects of Pb substitution on the properties of Bi-based Bi2−xPbxSr2CaCu2Oy superconductor with x = 0, 0.2, and 0.4 were investigated by means of DC electrical resistivity measurements. It has been found that the hole-carrier concentrations per-Cu ion of the samples change independently of Pb content.